2020
DOI: 10.37464/2020.374.123
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of care for people with multimorbidity: the development of a model for a nurse-led care coordination service

Abstract: Objective: To collaboratively develop a model of nurse-led care, within a multidisciplinary team and support continuity of care at the primarysecondary interface for people with multimorbidity.Background: Existing models of care are frequently based on a medical model, designed to manage a single disease condition, and thus pose a significant challenge to provide healthcare for people with multimorbidity. Particular design elements for models of care affecting the primary-secondary interface have been previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…Obviamente, não se pretende afirmar que houve incorreção nos planos de reabilitação em causa; cada um dos planos descritos cumpriu o seu propósito de forma idónea e de acordo com a situação clínica funcional que lhes serviu de base. Mas sendo o propósito máximo da continuidade de cuidados a fluidez entre contextos, centrando o processo na pessoa, percebe-se que neste caso particular a ligação e coordenação entre os diferentes serviços poderia ter tido maior expressão (6,7) .…”
Section: Resultsunclassified
“…Obviamente, não se pretende afirmar que houve incorreção nos planos de reabilitação em causa; cada um dos planos descritos cumpriu o seu propósito de forma idónea e de acordo com a situação clínica funcional que lhes serviu de base. Mas sendo o propósito máximo da continuidade de cuidados a fluidez entre contextos, centrando o processo na pessoa, percebe-se que neste caso particular a ligação e coordenação entre os diferentes serviços poderia ter tido maior expressão (6,7) .…”
Section: Resultsunclassified
“…A study in United States of America shows that 90% of patients hospitalized with chronic conditions had two or more chronic disease; of those hospitalized for acute potentially preventable diseases, almost 80% had multiple chronic diseases (Skinner et al, 2016). Improved care coordination, monitoring of patients' conditions and orientating patients to more appropriate health care settings can result in better health outcomes and more efficient use of health services (Davis et al, 2020; Skinner et al, 2016). In recent years, the concern for patients with multimorbidity has increased, and new ways of approaching these patients have emerged.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature that analysed the experience of hospital readmission in older adults concluded that their initial experience of hospitalization was characterized by feeling unprepared for discharge and uncertain of the future after discharge; namely, the perception that community services were not available or adequate (Blakey et al, 2017). A patient‐centred approach with greater involvement in the discharge process is desirable to better identify the needs of patients with multimorbidity and ensure continuity of care between the secondary and primary sectors for these patients (Davis et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nurse-led multicultural care coordination services are suitable for people with complex needs, including asylum seekers and people with multimorbidity (McBride et al 2016;Davis et al 2020). Nurses already receive cultural competency training, and previous studies have demonstrated that people from some CALD backgrounds trust nurse advice (Kay et al 2016;Parajuli et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We know it improves communication and coordination between service providers, improves preventative health activity, eases the primary care-hospital transition, improves team work and alerting of other team members of patient issues (Joshi et al 2013). Furthermore, when governance structures are in place to enable nurses to work across primary and secondary care sectors such as in M-CHooSe, the nurses are enabled to better coordinate care at the intersection of these sectors to get better outcomes and accessibility for their patients (Davis et al 2020). These result in better health outcomes, and we would expect similar outcomes from our work (Joshi et al 2013).…”
Section: Discussionmentioning
confidence: 99%